Genetic variability in wild and hatchery populations of commercially important fish: The common carp (Cyprinus carpio) - MARYAM AHMADI; HADISEH KASHIRI; ALI SHABANI; ABASALI AGHAEI MOGHADAM (Biodiversitas Journal of Biological Diversity, 2018)
Ahmadi M, Kashiri H, Shabani A, Moghadam AA. 2018. Genetic variability in wild and hatchery populations of commercially important fish: The common carp (Cyprinus carpio). Biodiversitas 19: 1468-1474. Common carp, Cyprinus carpio, is considered as one of the most important bony fish with high economic value in the Caspian sea. Since the population size of common carp has decreased during recent decades, restocking of the populations is done through releasing the hatchery-produced larvae into the Caspian Sea. In the present study, the genetic diversity of hatchery and wild populations of C. carpio was investigated using eight microsatellite loci (MFW7, MFW9, MFW13, MFW16, MFW17, MFW20, MFW26 and MFW28). A total of 145 different alleles were observed across all loci, with some of them being unique to each population. Although the allelic and gene diversity of hatchery populations tended to be lower compared to the wild populations, no significant differences (P>0.05) in genetic diversity parameters were observed among the wild and hatchery populations. In most cases, significant departure from Hardy-Weinberg equilibrium was observed, mainly because of the heterozygosity deficiency. Results from FST, RST and UPGMA analysis showed that the hatchery-reared population was the most differentiated and distant group. The results from this study are anticipated to provide important information for setting up more efficient strategies in conservation and restocking of C. carpio.